2019
DOI: 10.32598/bcn.9.10.385
|View full text |Cite
|
Sign up to set email alerts
|

Protective Role Of Apigenin Against Aβ25-35 Toxicity Via Inhibition Of Mitochondrial Cytochrome C Release

Abstract: Cognitive dysfunction is the most common problem of patients with Alzheimer Disease (AD). The pathological mechanism of cognitive impairment in AD may contribute to neuronal loss, synaptic dysfunction, and alteration in neurotransmitters receptors. Mitochondrial synapses dysfunction due to the accumulation of Amyloid Beta (Aβ) is one of the earliest pathological features of AD. The flavone apigenin has been reported to play some protective roles in AD through the anti-oxidative and anti-inflammatory properties… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…As shown in Figure 3D, the time to reach the exposed platform was not significantly different among all the groups, suggesting that the effect of apigenin on cognitive improvement was not related to visual or swimming abilities, but learning and memory abilities. Similarly, previous studies also demonstrated that apigenin improved spatial working memory function in behavioral tasks such as the Ymaze and Morris water maze tests in Aβ 25-35 -or isoflurane-induced in vivo model [33,34]. These findings demonstrated that apigenin could ameliorate cognitive dysfunction induced by scopolamine.…”
Section: Effect Of Apigenin On Morris Water Maze Test In Scopolamine-injected Micesupporting
confidence: 68%
“…As shown in Figure 3D, the time to reach the exposed platform was not significantly different among all the groups, suggesting that the effect of apigenin on cognitive improvement was not related to visual or swimming abilities, but learning and memory abilities. Similarly, previous studies also demonstrated that apigenin improved spatial working memory function in behavioral tasks such as the Ymaze and Morris water maze tests in Aβ 25-35 -or isoflurane-induced in vivo model [33,34]. These findings demonstrated that apigenin could ameliorate cognitive dysfunction induced by scopolamine.…”
Section: Effect Of Apigenin On Morris Water Maze Test In Scopolamine-injected Micesupporting
confidence: 68%
“…Hashemi et al [ 32 ] demonstrated that apigenin might have a protective effect on memory deficiency in specific behavioral tasks such as the Y-maze and Morris water maze, caused by kainite through anticonvulsant and anti-apoptosis activity. In another study, Nikbakht et al [ 33 ] reported that apigenin significantly ameliorated spatial working memory impairment induced by Aβ25-35 in the Y-maze test. Chen et al [ 34 ] identified apigenin as a potent suppressor of isoflurane exposure-induced learning and memory dysfunction in rats when tested within the Morris water maze test.…”
Section: Resultsmentioning
confidence: 99%
“…The main symptom of patients with AD is cognitive dysfunction. The cognitive impairment in AD may cause synaptic dysfunction, neuronal loss, and modification of neurotransmitter receptors (Nikbakht et al, 2019). Previous work reported that abnormal synaptic and dysfunction of network synchronous activity might contribute to hippocampal-dependent memory deficits in early AD models (Mayordomo-Cava et al, 2020).…”
Section: Discussionmentioning
confidence: 99%